2017
DOI: 10.1113/jp274164
|View full text |Cite
|
Sign up to set email alerts
|

Post‐translational palmitoylation controls the voltage gating and lipid raft association of the CALHM1 channel

Abstract: Emerging roles of CALHM1, a recently discovered voltage-gated ion channel, include purinergic neurotransmission of tastes in taste buds and memory formation in the brain, highlighting its physiological importance. However, the regulatory mechanisms of the CALHM1 channel remain entirely unexplored, hindering full understanding of its contribution in vivo. The different gating properties of CALHM1 in vivo and in vitro suggest undiscovered regulatory mechanisms. Here, in searching for post-translational regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 61 publications
4
39
0
Order By: Relevance
“…The extracellular ATP concentration was measured by the luciferin-luciferase reaction as previously reported ( 21 ). HeLa cells seeded at a density of 1.2 × 10 4 cells well −1 on 96-well cell culture plates (Corning Costar, Corning, NY, USA) were transfected with 0.6 µg pIRES2.AcGFP1 encoding WT or mutant OlCALHM1 cDNA or the empty vector using Lipofectamine 3000 (Thermo Fisher Scientific), according to the manufacturer’s instruction, and incubated for 4 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracellular ATP concentration was measured by the luciferin-luciferase reaction as previously reported ( 21 ). HeLa cells seeded at a density of 1.2 × 10 4 cells well −1 on 96-well cell culture plates (Corning Costar, Corning, NY, USA) were transfected with 0.6 µg pIRES2.AcGFP1 encoding WT or mutant OlCALHM1 cDNA or the empty vector using Lipofectamine 3000 (Thermo Fisher Scientific), according to the manufacturer’s instruction, and incubated for 4 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study reported that two cysteines in mouse CALHM1 are palmitoylated and associated with the post-translational regulation of the channel gating and localization ( 21 ). These two cysteines are completely conserved in the CALHM1 orthologs (Fig.…”
Section: Structure Of Olcalhm1mentioning
confidence: 99%
“…At a physiological [Ca 2+ ] o , CALHM1 is closed at the resting membrane voltage and needs strong depolarization to open ( V 1/2 ~82 mV at 5 mM [Ca 2+ ] o ), whereas in the absence of extracellular divalent cations, CALHM1 can be opened at more negative membrane voltages ( V 1/2 ~−76 mV), demonstrating that CALHM1 gating is activated by both Ca 2+ o reduction and depolarization [ 141 ]. Recently, S -palmitoylation, a reversible attachment of palmitate to Cys residues, at two intracellular Cys adjacent to the third and fourth transmembrane domains was demonstrated to modulate both the voltage sensitivity and lipid-raft association of the channel [ 143 ]. Other modes of CALHM1 activation remain to be identified.…”
Section: Calcium Homeostasis Modulator 1 (Calhm1)mentioning
confidence: 99%
“…The physiological significance of CALHM1 had remained elusive until the discovery of its ATP-releasing function. CALHM1 has been reported to be expressed in the brain [ 139 , 141 , 146 ], taste buds [ 27 , 143 , 147 ], nasal epithelium [ 105 ], bladder [ 145 ], other tissues [ 139 ]. In the human and mouse brains, its expression has been detected in hippocampal and cortical neurons, where it has been suggested to be involved in the [Ca 2+ ] o regulation of neuronal excitability by modulating membrane conductance [ 141 ], and in memory flexibility by modulating long-term synaptic potentiation via the phosphorylation of NMDA and AMPA receptors mediated by Ca 2+ influx through the channel [ 148 ].…”
Section: Calcium Homeostasis Modulator 1 (Calhm1)mentioning
confidence: 99%
“…Bodily and cellular functions are controlled by various factors including ions such as Na + , K + , Ca 2+ , Mg 2+ , Zn 2+ , and Cl − [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. On the one hand, pH (−log[H + ]) is recognized as one of classical items considered to be already fully understood in roles and mechanisms of homeostasis.…”
Section: Variety Of the Interstitial Fluid Phmentioning
confidence: 99%